Follicular fluid and plasma lipidome profiling and associations towards embryonic development outcomes during ART treatment - Jiang, Yingxin Celia; Che, Qi; Lu, Xinmei; Liu, Miao; Ye, Yao; Cao, Xiang; Li, Xushuo; Zhan, Yanxia; Dong, Xi; Cheng, Yunfeng; O’Neill, Christopher (Frontiers in Endocrinology, 2024)
IntroductionIt is well acknowledged that lipids assume a critical role in oocyte maturation and early embryonic metabolism, this study aimed to evaluate the relationship between the lipid composition of plasma and follicular fluid (FF), and the consequences of embryonic development. This study compared the lipidomic profiles of paired plasma and FF samples obtained from sixty-five Chinese women who underwent assisted reproductive technology (ART) treatments.MethodsNon-targeted lipidomics analysis.ResultResults not only indicated similarities in lipid composition between these biofluids, but also revealed a number of unique differences. The biomatrix distinction was found to be primarily driven by lipids belonging to the lysophosphatidylcholines (LPC), phosphatidylethanolamines (PE), ether PE, and triglyceride (TG) classes. In addition, specific species from these subclasses were discovered to be correlated with embryo development outcomes during ART. Notably, the composition of the fatty acyl chains appeared to play a crucial role in these associations. Furthermore, thirteen plasma lipid variables were identified, represented by Phosphatidylcholine 18:014:0 and PE P-18:020:1, which correlated with successful blastocyst formation (BF).DiscussionThe present study demonstrated that FF has a distinctive lipid composition, setting it apart from plasma; and the association observed with embryonic development underscored an important role of lipid composition in the healthy development of oocytes.